(untitled) (Bangladesh Journal of Medical Science, 2021)
Background: Polycystic ovary syndrome (PCOS) affects 5-10% of reproductive age women and it is a common cause of infertility in young women. Most of the infertile women with PCOS are overweight or obese. Obesity or excess fat aggravates the endocrine and metabolic dysfunction in women with PCOS. Weight management is the first line measure advised to infertile PCOS women who are overweight or obese. The objective of the study was to explore the association of obesity with the clinical, endocrine and metabolic parameters in infertile women with polycystic ovary syndrome in Bangladesh. Methodology: This was a cross sectional study of 126 consecutive infertile women with polycystic ovary syndrome attending the Infertility unit of the Department of Obstetrics and Gynecology at Bangabandhu Sheikh Mujib Medical University from January 2017 to December 2017.Obesity groups were defined by BMI thresholds specific for the South Asian population. Results: The mean body mass index (BMI) was 26.58±3.18 kg/m2and mean waist circumference was 91.07±9.5 cm. There was highly significant association of obesity with waist circumference and fasting insulin. BMI at or above 25kg/m2 was significantly associated with acanthosis nigricans, hyperandrogenemia and hyperinsulinemia, whereas BMI at or more than 23kg/m2 was significantly associated, in addition, with insulin resistance and metabolic syndrome. Conclusion: Obesity is associated with hyperandrogenemia, hyperinsulinemia, insulin resistance and metabolic syndrome in infertile women with polycystic ovary syndrome. Bangladesh Journal of Medical Science Vol.20(4) 2021 p.864-870